Multilateralizacja polityki konkurencji w ramach WTO - Kąkol, Magdalena (Multilateralisation of Competition Policy within WTO, 2009)
The paper focuses on presentation of results of international co-operation, undertaken within GATT and WTO, leading to multilateral competition rules and determining causes of the lack of compromise on that matter between WTO member countries. In the conclusion, the author states that the main difficulties in reaching a WTO multilateral competition agreement derive from: 1) negotiating competition issues in connection with trade concessions, 2) reluctance of the United States to accept binding competition rules, 3) fears of developing countries that a new agreement will not address their concerns regarding anti-competitive behaviour by multinational firms and will not provide them with suitable concessions, 4) supporting different aims of competition policy by WTO countries. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 634-645